FIGURE 5. A–D in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
FIGURE 5. A–D, Dromia erythropus (Edwards in Catesby, 1771). A, B, Male, cl 16 mm, cw 18 mm (MZUSP 40358), habitus dorsal and ventral views, respectively. C, Megalopa, cl 5 mm, cw 4.5 mm, habitus dorsal view (MZUSP 40354). D, Male, cl 21 mm, cw 23.5 mm (MZUSP 33349). Scales: A, B, 10 mm. C, 2.5 mm. Photographs by A. Pol. Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 14, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155